PSIX-18 Laurate and its glycerol monoester, monolaurin, as potential additives to control Listeria monocytogenes and tetracycline resistant Enterococcus faecalis in air-exposed silage. (30th November 2020) - Castillo-Castillo, Yamicela; Ontiveros, Marina; Scholljegerdes, Eric J; Anderson, Robin; Arzola-Alvarez, Claudio; Salinas-Chavira, Jaime; Hume, Michael; Beier, Ross C; Poole, Toni L; Nisbet, David; Ordoñez, Perla L; Ruiz-Barrera, Oscar
Abstract: Silages can harbor pathogenic and antimicrobial resistant microbes which risk infection of food-producing animals. Livestock producers need effective yet environmentally friendly interventions to preserve the feed value of these fermented materials. Medium chain fatty acids such as laurate and its glycerol monoester, monolaurin, are potent inhibitors of many Gram-positive bacteria and when tested at 5 mg/mL in anaerobic cultures (n = 3/treatment) inoculated with 10 5 colony forming units (CFU) of Listeria monocytogenes and grown at 37 o C in ½ strength Brain Heart infusion broth achieved near complete elimination of viable cells after 6 h compared to a 2.2 ± 0.1 log10 CFU/mL increase observed in controls. Culture of a tetracycline-resistant Enterococcus faecalis with 5 mg laurate/mL likewise achieved near complete elimination of viable cells (5 log10 CFU/mL) by 6 h incubation. The bactericidal effect of 5 mg monolaurin was less against E. faecalis, achieving a decrease of 1.8 ± 0.2 log10 CFU/mL and not decreased further after 24 h. When tested against air-exposed silage, pH 7.53 (4 g), mixed with 4 mL water, 5 mg laurate or monolaurin decreased viability of experimentally-inoculated L. monocytogenes (10 5 CFU/g silage) more (P < 0.05) than untreated controls after 24 h aerobic incubation (22 o C), with viable counts being decreased 6.3 ± 0.1, 5.9 ± 0.8 and 4.5 ± 0.1 log10 CFU/g, respectively. In contrast, viable recovery of the experimentally-inoculated (10 5 CFU/g) tetracycline-resistant E. faecalis was reduced more (P < 0.05) than controls (decreased 0.7 ± 0.1 log10 CFU/g) after 6 h incubation when similarly tested with laurate and monolaurin (1.7 ± 0.5 and 3.0 ± 0.9 log10 CFU/g, respectively) but counts after 24 h were similar, decreasing on average 2.0 ± 0.5 log10 CFU/g). Results indicate laurate and monolaurin may be useful in killing L. monocytogenes and tetracycline-resistant E. faecalis during silage feed-out.